Personal characteristics of students with learning difficulties in the light of Eysenck's theory of personality - Yaseen, Mahmoud Mohamed Mahmoud (Journal of Educational and Psychological Sciences, 2022)
The study aimed to identify the characteristics of students with learning difficulties on the Eysenck Personality Scale, and the study sample included (24) students who frequent the Charitable Society for Learning Difficulties, their ages ranged between (8 to 15) years. And the Eysenck personality scale, and the results indicated that the children’s personality dimensions were at a medium level, and significant differences were found between extraversion and neuroticism at the significance level of 0.01 in favor of extraversion, and there were differences between extraversion and lying at the level of 0.05 in favor of extroversion, and there were no differences between lying and neuroticism. The results indicated that there are no statistically significant differences due to the child's Gregorian order, as well as the presence of apparent differences due to the difference in the school grade, and the test results showed that there are no statistically significant differences attributable to the grade, and there were apparent differences due to the type of difficulty in the child, and the results showed , There were no statistically significant differences due to the type of difficulty, and the results also indicated that there were statistically significant differences at the 0.05 level in the neuroticism dimension in favor of Riyadh students in the difference between Rayya students Z and Medina, and there are no significant differences between students of Medina and Jeddah and between students of Riyadh and Jeddah.
Keywords: personality traits; learning difficulties; Eysenck's theory of personality